Leadership multiplicities before and during the post-truth era - Leonel Prieto (Administrative Sciences, 2019)
Drawing from the ontology of the lack (Laclau and Mouffe 1985), aesthetic theory (Adorno 1997); practice theory (Bourdieu 2002), art perception theory (Bourdieu 1968), and storytelling theory (Boje 2001), we discuss leadership multiplicities and post-truth era phenomena. We conceptualize leadership as a heterogeneous field with an evolving incomplete set of contested narratives, at different development stages, entertained by different players. In the continuous re-occupation of the lack exists tensions, contradictions and conflicts within and between players' narratives. This situation generates a large variability that requires acknowledgement, promotion, and some management. We relate our discussion to education. We suggest ways to create unity within diversity and resolve some of these contradictions and tensions. The concept of parallax (Zizek 2006), which offers a new gaze, illustrates how to configure sets of related leadership narratives.
Keywords: 350; leadership; multiplicity; post-truth phenomena; education; parallax